Meningkatkan Pengetahuan dan Minat Gen-Z untuk Berkarir di Dunia Startup dengan Webinar “Startup for Gen-Z: Is It Possible?” - Slamet Slamet; Purwono Purwono; Sony Kartika Wibisono; Bala Putra Dewa (LPPM Universitas Harapan Bangsa Purwokerto, 2022)
Indonesia is one of the countries with the best startup developments in the world which ranks 6th in the country with the highest number of startups. However, the quality of Indonesian human resources, which are able to meet the qualifications of startup companies, is still low. To that end, the devotees do community service, namely by holding a webinar with the theme